MENGIDENTIFIKASI DITERBITKANNYA ‘SECOND HOME VISA’ BAGI ORANG ASING GUNA MENINGKATKAN PEREKONOMIAN INDONESIA - Annisa Niazela; Michella Theresia; Panca Cahaya Kusuma (Jurnal Ilmiah Advokasi, 2023)
The existence of a visa policy in Indonesia is one way to select foreigners who want to enter Indonesia. The existing selection process is adjusted to the category of foreigners who want to enter the territory of Indonesia. In this case, the latest policy of the Directorate General of Immigration regarding the granting of visas for foreigners in Indonesia is the existence of a secondhome visa policy. The second home visa is a policy aimed at allowing foreigners to be more interested in coming to Indonesia and making long-term investments to improve the country's economy. However, as with many other policies, many things are in fact not in line with the expectations of implementing these policies. Therefore, a competent study is needed to identify how effective the granting of a second home visa is for foreigners who want to enter Indonesian territory. This research uses normative research methods with an approach that is carried out on the basis of materials to study theoretical problems related to concepts, views, principles, legal doctrines, legal rules and systems. So as to conclude that the implementation of the second home visa policy in Indonesia still has to be further studied by identifying the effectiveness of the second home visa itselfKeywords : Second Home Visa, Foreigner, Directorate General of Immigration